Wybory prezydenta RP w 2025 roku – podstawy prawne ………. 51 - Solarz, Katarzyna; Aronowska, Adrianna (Wybory prezydenckie w Polsce w 2025 roku w świadomości najmłodszego elektoratu województwa małopolskiego, 2025)
PRESIDENTIAL ELECTIONS IN THE REPUBLIC OF POLAND IN 2025 – LEGAL FOUNDATIONSThe subject of analysis in the chapter entitled Presidential Elections in the Republic of Poland in 2025 – Legal Foundations is the identification of the principal normative acts legitimizing presidential elections in Poland. The analysis focuses on legal instruments containing the most significant provisions governing the organization of presidential elections, namely: the Constitution of the Republic of Poland of 2 April 1997, the Electoral Code Act of 5 January 2011, and the Resolution of the Marshal of the Sejm of the Republic of Poland of 15 January 2025 on the ordering of the presidential election. The chapter presents an examination of these legal provisions in accordance with the established hierarchy of sources of law. The aforementioned legal acts constitute the legal foundation for the elections and define the procedures for announcing, conducting, and determining the results of the election of the head of state. The analysis of the selected legal instruments leads to the conclusion that, in terms of the letter of the law, the 2025 presidential election in Poland satisfies all the requirements derived from the standards of democratic elections.